Rapid detection of trace Cu2+ using an l‐cysteine based interdigitated electrode sensor integrated with AC electrokinetic enrichment. Issue 20 (14th June 2019) - Qi, Haochen; Zhao, Meiqi; Liang, Huaguo; Wu, Jayne; Huang, Zhengfeng; Hu, Anming; Wang, Jian; Lu, Yingchun; Zhang, Jian
Abstract: Copper is an indispensable trace element for human health. Too much or too little intake of copper ion (Cu 2+ ) can lead to its own adverse health conditions. Therefore, detection of Cu 2+ is always of vital importance. In this work, a simple sensor was developed for rapid detection of trace Cu 2+ in water, in which L‐cysteine (Cys) as a molecular probe was self‐assembled on a gold interdigital electrode to form a monolayer for specific capture of Cu 2+ . The interfacial capacitance of interdigital electrode was detected to indicate the target adsorption level under an AC signal working as the excitation to induce directed movement and enrichment of Cu 2+ to the electrode surface. This sensor reached a limit of detection of 4.14 fM and a satisfactory selectivity against eight other ions (Zn 2+, Hg 2+, Pb 2+, Cd 2+, Mg 2+, Fe 2+, As 3+, and As 5+ ). Testing of spiked tap water was also performed, demonstrating the sensor's usability. This sensor as well as the detection method shows a great application potential in fields such as environmental monitoring and medical diagnosis.